IMAM AN-NASA’I (Mengurai Biografi dan Perjalanan Intelektual Imam An-Nasa’i) - Azwir, Azwir (Lembaga Jurnal dan Seminar Universitas Pembangunan Panca Budi, 2017)
History has mentioned how the books of hadith have a considerable time span from the original source (Rasulullah saw.,). In addition history also notes how many hadiths dhaif (weak) and false traditions (maudhu ') who have infiltrated into the treasures of Hadith at the time not yet booked. Faced with this problem the scholars fought hard to select the hadith, both from sanadnya and matannya. In this paper, we will describe a biography of a prominent scholar of hadith in the eyes of the Islamic scientists, theImam An-Nasa'i.